Toll-Like Receptors and Viruses: Induction of Innate Antiviral Immune Responses - Xagorari, Angeliki (Bentham Open, 2008)
Induction of antiviral innate immune responses depends on a family of innate immune receptors, the Toll-like receptors (TLR). TLR mediate the antiviral immune responses by recognizing virus infection, activating signaling pathways and inducing the production of antiviral cytokines and chemokines. ssRNA and dsRNA viruses can be recognized by TLR7/8 and TLR3, respectively. TLR receptors are also involved in the recognition of viruses containing genomes rich in CpG DNA motifs as well as envelope glycoproteins. Cytoplasmic recognition of dsRNA by RNA helicases such as RIG-I and MDA5 provides another means of recognizing viral nucleic acid. In order to counteract the innate host immune system viruses evolved mechanisms that block recognition and signaling through pattern recognition receptors, such as TLRs and RNA helicases. Recently, TLR agonists represent a promising approach for the treatment of infectious diseases. This review will focus on the current knowledge of TLR-mediated immune responses to several viral infections.